PERTANIAN VERTIKAL SEBAGAI RESPONS PEDAGANG PASAR TRADISIONAL DI KECAMATAN KEMBANGAN TERHADAP PERUBAHAN POLA PERDAGANGAN DAN GAYA HIDUP MASYARAKAT - Justin, Justin; Winata, Suwardana (Jurusan Arsitektur dan Perencanaan, 2024)
Traditional markets are places for buying, selling and bargaining activities. However, currently people's interest in traditional markets is decreasing due to changes in people's lifestyles. This has a big impact on traditional market traders in urban areas, especially in the Kembangan District. Currently, people are starting to pay attention to their health through the quality of the food they consume so that the quality of the freshness of the fresh ingredients can determine consumer trust in traders. Apart from that, there has been a change in trading patterns, from initially conventional trading to now being completely digital, resulting in the loss of the role of traders who are distributors liaising between producers and consumers. This change in people's lifestyles has forced competitors such as modern markets and online traders to start selling fresh goods to attract people's interest. This sense of empathy for the problems of traditional market traders in the Kembangan area creates a desire to learn more about traditional traders and markets so that they can find solutions to these problems. In the process of empathy, an idea was discovered that could turn traders into